Peran Gereja Masehi Injili di Halmahera dalam Pendidikan Politik Bagi Anggota Jemaat - Hohakay, Karwanto Oktofianus; Itje, Tomi; May, Oscar Jeferson Scheitzer; Ice, Demianus (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This study examines the role of the Evangelical Christian Church in Halmahera (GMIH) in providing political education to its congregation ahead of the 2024 General Election in Tobelo District, focusing on how the church educates its members about politics following Christian values. The qualitative research method, with a case study approach, involves in-depth interviews with five GMIH synod leaders. Data were analyzed using thematic analysis techniques. The results indicate that GMIH has successfully implemented effective political education, emphasizing the understanding of rights and obligations in democracy, integrating Christian values, and using information technology. The church also plays a crucial role in maintaining the harmony of the congregation and avoiding practices of money politics. In conclusion, the political education provided by GMIH enhances the congregation's awareness and ethical political participation, supporting the church's goal of promoting justice and goodness in society.